Defining the Urban : Interdisciplinary and Professional Perspectives - Iossifova, Deljana; Doll, Christopher; Gasparatos, Alexandros (London : Taylor and Francis, 2017)
What is "urban"? How can it be described and contextualised? How is it used in theory and practice? Urban processes feature in key international policy and practice discourses. They are at the core of research agendas across traditional academic disciplines and emerging interdisciplinary fields. However, the concept of "the urban" remains highly contested, both as material reality and imaginary construct. The urban remains imprecisely defined. Defining the Urban is an indispensable guide for the urban transdisciplinary thinker and practitioner. Parts I and II focus on how "Academic Disciplines" and "Professional Practices," respectively, understand and engage with the urban. Included, among others, are Architecture, Ecology, Governance and Sociology. Part III, "Emerging Approaches," outlines how elements from theory and practice combine to form transdisciplinary tools and perspectives. Written by eminent experts in their respective fields, Defining the Urban provides a stepping stone for the development of a common language$1 (Ba shared ontology$1 (Bin the disjointed fields of urban research and practice. It is a comprehensive and accessible resource for anyone with an interest in understanding how urban scholars and practitioners can work together on this complex theme.s
chapter 1 Defining the urban: Why do we need definitions? / Deljana Iossifova -- part Part 1 Academic disciplines -- t Hyun Bang Shin -- chapter 4 Anthropology: The death and rebirth of urban anthropology / Setha M. Low -- r Lynne C. Manzo -- part PART II Professional practices -- r Nestor M. Davidson -- part PART III Emerging approaches -- chapter 17 Geospatial techniques / Christopher N. H. Doll -- chapter 18 Urban political ecology: Landscapes of power / Anna Zimmer -- chapter 19 Urban metabolism: Conceptualizing the city as an organism / Alexandros Gasparatos -- chapter 20 Transition theories / Peter J. Marcotullio -- chapter 21 Complexity science: The urban is a complex adaptive system / Ulysses Sengupta -- chapter 22 Science fiction: The urban in posthuman science fiction / Bodhisattva Chattopadhyay -- part PART IV Synthesis -- chapter 23 Defining the Urban: A quixotic pursuit / Deljana Iossifova.
Keywords: Sociology, Urban; Cities and towns; Architecture; Urban Design; Urban Geography; Urban Sociology